DEATH RATES AND NEUROCOGNITIVE FUNCTION IN PEOPLE WITH SCHIZOPHRENIA SPECTRUM ILLNESSES - Manish Kumar Meel (Journal of Biomedical and Pharmaceutical Research, 2020)
Background: Sedentary behavior and a relative lack of physical activity in SSD patients may be one explanation for greater incidences of somatic sickness. In the past, we discovered that lower levels of physical and social engagement in SSD were predictive of a shortened life expectancy 18 years following study admission. Additionally, in the patient group with severe neurocognitive abnormalities, there was a stronger correlation between activity level and life expectancy. Material and Methods: This study was conducted in the dept. of Psychiatry. Briefly, men and women suffering from SSD were recruited from the outpatient clinics in the Hospital region. Two thirds of all eligible patients on this geographic catchment area were included at baseline. The participants were required to be in a stable clinical condition. Exclusion criteria were age below 18, mental retardation precluding the ability to give informed consent, past or present neurological illness, and significant past or present use of alcohol or illegal substances. Each participant gave their written informed consent to participation. Result: The deceased group had much more severe neurocognitive deficits across nearly all domains, according to the results, when compared to the living group. There were no variations in the groups’ function levels, sex, remission status, or psychosis symptoms. The best indicators of survival status were executive function and short-term verbal memory. Conclusion: According to our research, cognitive dysfunction in SSD patients has a serious impact on somatic morbidity and death. Caretakers need to be aware of the additional load cognitively impaired individuals carry in terms of heightened susceptibility to illness. These patients should receive regular standardized somatic tests as part of mental health check-ups, and the physicians should be especially aware of communication issues in these patients. Keywords: Death Rates, Neurocognitive Function, Schizophrenia Spectrum Illnesses